Thermal analysis of filling PP with core–shell nanoparticles and rheological behaviour. (23rd February 2016) - Liu, Ling; Wang, Xiuli; Xie, Lisi; He, Sile
Abstract : Shell cross-linked core–shell nanoparticles (SCCSN) with organic montmorillonite as the core and cross-linked polymethacrylate (PMMA) as the shell were prepared through seeded emulsion polymerisation. Scanning electron microscopy and transmission electron microscopy images of SCCSN show that each of the SCCSN is spherical with core–shell structure. The thermal properties and rheological behaviour of polypropylene (PP)/SCCSN composites with different proportions of SCCSN were systematically studied using a thermogravimetric analyser and an RT-2000 high-pressure capillary rheometer, respectively. The existence of SCCSN improves the thermal properties of PP, and the thermostability of the composite increases with increasing SCCSN content. The formed composite is a non-Newtonian pseudoplastic fluid with a similar processing behaviour to PP. The rheological parameters (e.g. shear stress, apparent viscosity and flow activation energy) of the composite decrease as SCCSN fills in. These data indicate that using SCCSN does not affect the processing fluidity of PP but improves its processability.